Synthesis, characterization, crystal structure, and electrochemical study of zinc(II) metal-organic framework. Issue 11 (2nd November 2019) - Omkaramurthy, B. M.; Krishnamurthy, G.
Abstract: A zinc(II) metal-organic framework, [Zn (BDC) (MI) (DMF) or Zn-MOF] (BDC=Benzene 1, 4 di-carboxylic acid, MI=Methylimidazole and DMF=N, N-dimethylformamide) has been synthesized by solvothermal method using mixed ligands. The Zn-MOF has been characterized by powder X-ray diffraction, single-crystal X-ray diffraction, Thermo gravimetric analysis, Infrared spectroscopy, and cyclic voltammetry. In Zn-MOF, Zn–N bond lengths were 2.010 (2) and 2.044 (2) Å, Zn–O bond lengths are 1.965 (2) and 1.980 (18) Å and the space group is P-1. These 3 D sheets are connected by Carboxylate groups of bdc and Mi ligands are coordinated to Zn (II) cation in a monodentate manner, forming 3 D frameworks of triclinic geometry. The cyclic voltammetry measurements were performed at different scanning rates (10–100 mVs −1 ) in the potential range is –0.1–0.1 mVs −1 in 6 M KOH solution.